Поэма Пушкина «Граф Нулин» = Pushkin's "Count Nulin" Anew Опыт комментированного чтения = Reconstructing a First Reading - Leibov, Roman (University of Tartu Press, 2023)
This book examines different contexts relevant to Pushkin in 1825 when the poem "Count Nulin" was written. Its bulk consists of studies devoted to (1) various manuscripts of the text, (2) the issue of censorship and the publication of "Count Nulin" during Pushkin's life, (3) the biographical context for the poem's creation, (4) the role of the text in literary polemics and (5) reactions of critics (as well as readers) during Pushkin's lifetime. Developing the idea of Boris Eikhenbaum, R. Leibov proposes that the text was addressed primarily to members of the Petersburg literati who made up the "Poliarnaia zvezda" (Polar Star) circle. Moreover, Leibov suggests that, in "Count Nulin", Pushkin purposefully exaggerated those literary techniques that attracted criticism in "Eugene Onegin", making "Count Nulin" function as a self-parody. The final section of the book is composed of commentary on the poem, combining a traditional focus on the interpretation of fragments of the text with an emphasis on its overall composition, as well as description of the changing rhetorical and narrative strategies of its author.